Changes in working hours are driving earnings inequality - Mattis Beckmannshagen; Carsten Schröder (DIW Weekly Report, 2022)
According to Socio-Economic Panel (SOEP) data, inequality in gross monthly earnings in Germany increased significantly between 1993 and 2003 and has been stagnating at a high level since 2008. As this Weekly Report shows, the increase is not being driven by higher hourly wage inequality, but rather by working hours: In recent years, employees with a high hourly wage work more than previously compared to employees with a low hourly wage. In particular, this applies to two groups whose share of the workforce has increased significantly in recent years: employed women and service sector employees. Had employees been able to work their desired number of hours, the rise in inequality would have been more moderate. A better work-life balance and more opportunities to increase working hours in the low-wage sector could counteract this trend.
Keywords: D63; J22; J31; 330; Earnings inequality; Working hours; Hours mismatch; Part-time work; Decomposition analysis